Epidemiology of pertussis in children hospitalised with respiratory tract infection - Muloiwa, Rudzani (Department of Paediatrics and Child Health, 2021)
The availability of an effective vaccine against Bordetella pertussis substantially reduced the morbidity and mortality from pertussis, however, in the last decade there appears to have been a substantial increase in pertussis cases as reported mainly in high income countries. Although it is believed that the greatest burden of pertussis, including deaths, is in low- and middle-income countries (LMICs), there seem to be little data available to back this up. This thesis set out to find data that will give some insight into the burden of pertussis in a low- and middle-income setting in infants and children with severe lower respiratory tract infection (LRTI). Given the paucity of data in LMICs, the thesis starts by systematically searching for existing data that will give some indication of the possible extent of the pertussis problem in these countries. Secondly, a prospective study was conducted at a children's hospital. As hospital admission is a marker of severe disease, these children were targeted as the appropriate population in which to meaningfully conduct a primary study on the burden of pertussis. In addition to quantifying the burden by describing the prevalence of confirmed pertussis in this group of children, the study set out to look for potential factors that may be associated with increased risk of pertussis. LRTI are now commonly known to be associated with identification of multiple organisms in respiratory samples, this study aimed to also look at organisms that are detected with Bordetella pertussis; and investigate whether this association was in any way associated with severe disease or negative outcomes. Finally, as data has been emerging that in the context of immunisation, the clinical presentation of pertussis may no longer be following a classical pattern, this study hoped to identify clinical features that could be used to develop a more reliable clinical case definition of pertussis. 2 Chapter 1 gives a background that justifies the undertaking of this study as well as give a summary of the methods used to answer the question of the thesis. The chapter also gives an indication of the structure that the thesis follows. In chapter 2 a systematic review quantifies the burden of pertussis in LMICs using the best available data. In chapter 3 the burden of pertussis due to the two organisms known to cause the disease, Bordetella pertussis and Bordetella parapertussis, is described in some detail. In both this chapter and the earlier mentioned systematic review (chapter 2), the burden of pertussis is stratified by subgroups to identify potential risk factors. The issue of risk is formally and specifically taken up in the chapter that follows (chapter 4) where potential risk factors are analysed, and the independent impact for some of these factors is established. The last two results chapters (chapters 5 and 6) deal respectively with the conundrum of finding other respiratory organism in the same specimen with Bordetella pertussis and failure to find useful clinical criteria that can help with improved diagnosis of pertussis, specifically in children presenting with acute severe lower respiratory tract infection. While there is no established pattern noted between pertussis and most organisms, a few give signals of being independently associated with Bordetella pertussis even if the clinical relevance is not clear at the moment. In the final chapter of the thesis (chapter 7) I conclude the thesis by making an argument that although there are still knowledge gaps, the thesis gives a clear indication that pertussis remains a serious problem in LMICs especially for some groups that show increased risk of the disease or its severe consequences.